Development of Soil & Water Assessment Tool Application In Krueng Aceh Watershed Review - Ikhwali, M Faisi; Ersa, Nanda Savira; Khairi, Alfin; Prayogo, Wisnu; Wesli, Wesli (UNIVERSITAS MALIKUSSALEH, 2022)
Abstract The problem of the water availability has become a global issue so that it needs a tool for water management such as the Soil and Water Assessment Tool (SWAT). This study aims to measure how far the uses and developments of the SWAT model in the Krueng Aceh watershed. This paper reviewed applications of SWAT Model in Krueng Aceh Watershed. The developments data were obtained from five publications. This study has limitations in assessing the performance of the SWAT developed in the Krueng Aceh watershed/sub-watershed because not all publications report on the calibration or validation process. From the search results, there is one modeling application that performs the calibration process with statistical parameters on a daily scale and the other three papers on monthly data. The availability of observation data has not had a long time series makes researchers face limitations in improving the model performances. Keywords: SWAT, Hydrological Model, Water, Soil Abstrak Masalah ketersediaan air telah menjadi isu global sehingga diperlukan suatu alat untuk pengelolaan air seperti Soil and Water Assessment Tool (SWAT). Penelitian ini bertujuan untuk mengukur sejauh mana pemanfaatan dan perkembangan model SWAT di DAS Krueng Aceh. Artikel ini mengulas penerapan Model SWAT di DAS Krueng Aceh. Data perkembangan diperoleh dari lima publikasi mengenai Model SWAT. Kajian ini memiliki keterbatasan dalam menilai kinerja SWAT yang dikembangkan di DAS/sub-DAS Krueng Aceh karena tidak semua publikasi melaporkan proses kalibrasi atau validasi. Dari hasil pencarian, terdapat satu aplikasi pemodelan yang melakukan proses kalibrasi dengan parameter statistik pada skala harian dan tiga aplikasi lainnya pada data bulanan. Ketersediaan data lapangan yang belum memiliki data time series yang panjang membuat peneliti menghadapi keterbatasan dalam meningkatkan perfoma model. Kata Kunci: SWAT, Model Hidrologi, Air, Tanah